Propriedades e aplicações de revestimentos de óxidos metálicos obtidos por oxidação eletrolítica a plasma e dopagem anódica utilizando resíduo de lama vermelha - Araújo, Patrícia dos Santos (Universidade Federal de São Carlos, 2023)
Plasma Electrolytic Oxidation (PEO) is a metal processing technique where a high potencial difference is applied between two electrodes, cathode and anode. During this process there is a phenomenon of dielectric breakdown caused when the thickness of the oxide layer that forms reaches a limit and causes micro discharges to appear throughout the surface of the material that sinter and crystallize the formed oxide adhered to the substrate. The oxide layer produced under these conditions can have characteristics such as high mechanical strength or photoactivity. Processing conditions, such as composition, concentration or temperature of the electrolyte used during the formation of coatings, affect the composition and morphology of the produced coatings, altering their properties. This work presents results of the process of surface treatment of Niobium metal under PEO conditions, using a system consisting of a direct current source in galvanostatic regime and temperature control of the electrolyte. The photocatalytic properties of the coatings are also observed. The work can be divided into three parts: 1) investigation of the influence of different electrolytes on the anodizing curve of the synthesis of Nb2O5 coatings. Niobium substrates after anodization in acid medium (C2H2O4 and H3PO4) and basic medium (KOH) were characterized and tested for photoactivity; 2) investigation of the insertion of different amounts in mass percentage of Red Mud in C2H2O4 solution, during the anodizing process. Red Mud is an alkaline residue from the aluminium industry and was used as a dopant; 3) the study of the temperature and composition of the electrolytes in the oscillations of potential and photoactivity of the coatings. In this step, the temperature variation of the electrolyte in the synthesis of the coatings was investigated using different compositions of electrolytes (C2H2O4 at 2 and 25°C, H3PO4 at 15 and 30 °C, KOH at 15 and 25°C and C2H2O4+1% of mud at 15 and 25°C). The samples were characterized by techniques such as scanning electron microscopy (SEM), energy dispersive spectrometry (EDS), X-ray diffraction (XRD) and diffuse reflectance spectroscopy (DRS). The photocatalytic efficiency was investigated using photodegradation tests in a UV camera with samples in contact with an aqueous solution of Methylene Blue (MB) and Rhodamine B (RhB). During the synthesis in different types of electrolytes, different behaviour of temperature and voltage curves (V) as a function of charge (C) were observed. As a consequence, the samples presented morphology and varied chemical and structural composition according to the parameters of synthesis and addition of dopant, the samples anodized with electrolyte containing 0.1 mol.L-1 solution of C2H2O4 and addition of sludge up to 0.75% , showed superior photocatalytic efficiency compared to other studied conditions. This result was explained by the characterizations that showed morphology with pores of regular size and shape with distribution over the entire surface, formation of orthorhombic Nb2O5, bang gap estimated between 3.12 to 3.27 eV. After the inclusion of the red mud to the electrolyte, elements such as Al and Si were found in the coatings produced and the doping of a small % of these elements on the surface of the coatings proved to be effective in increasing the degradation rate of the MB dye in the first 60 minutes of the test.
Properties and applications of metal oxide coatings obtained by plasma electrolytic oxidation and anodic doping using red mud residue
Keywords: Oxidação Eletrolítica a Plasma; Fotocatálise Heterogênea; Dopagem anódica; Lama Vermelha; Nb2O5; Plasma Electrolytic Oxidation; Heterogeneous Photocatalysis; Anodic Doping; Red Mud; CIENCIAS EXATAS E DA TERRA::QUIMICA::FISICO-QUIMICA